Effects of Perinatal Stroke on Executive Functioning and Mathematics Performance in Children. (February 2022) - Li, Eliza; Smithson, Lisa; Khan, Muhammad; Kirton, Adam; Pei, Jacqueline; Andersen, John; Yager, Jerome Y.; Brooks, Brian L.; Rasmussen, Carmen
The goal of this study was to examine executive functioning, math performance, and visuospatial processing skills of children with perinatal stroke, which have not been well explored in this population. Participants included 18 children with perinatal stroke (aged 6-16 years old) and their primary caregiver. Each child completed standardized tests of executive function and visuospatial processing skills, Intelligence Quotient (IQ), and math achievement. Performance on executive function, IQ, math, and visuospatial processing tests was significantly lower in children with perinatal stroke when compared to normative means. Poorer inhibitory control was associated with worse math performance. Increased age at testing was associated with better performance on visuospatial ability (using standardized scores), and females performed better than males on a test of inhibitory control. Children with perinatal stroke displayed a range of neuropsychological impairments, and difficulties with executive function (inhibition) may contribute to math difficulties in this population.